Heavy hydrocarbon hydroprocessing catalyst and preparation and use method thereof
By developing high porosity boiling bed catalysts, using co-grinding and controlled calcining technologies, the problems of insufficient activity of existing catalysts and high precipitate yields are solved, and high conversion and low precipitate yields of heavy hydrocarbons are achieved.
Patent Information
- Application Number
- CN202180053747.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-01
- Filing Date
- 2021-09-01
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-09-01
AI Technical Summary
The existing catalysts have insufficient activity when treating heavy hydrocarbons, resulting in low conversion of asphalt components and high yield of precipitate, making it difficult to meet industrial needs.
A high porosity boiling bed catalyst is developed to combine components such as alumina, molybdenum and nickel through co-grinding and controlled calcining technology, and to form a catalyst with high porosity and enhanced catalytic properties using high molecular weight polyacrylamide.
High conversion rate and low precipitate yield of heavy hydrocarbon raw materials are achieved, and the activity and efficiency of the catalyst are significantly improved.
Smart Images

Figure BDA0004101557920000151 
Figure HDA0004101557930000011
Abstract
Description
[0001] Citation of Related Applications
[0002] This application claims priority to U.S. Provisional Patent Application Serial No. 63 / 073015, filed on September 1, 2020, entitled “A HEAVY HYDROCARBONHYDROPROCESSING CATALYST AND METHOD OF MAKING AND USING THEREOF,” and the entire text of that provisional application is hereby incorporated by reference herein.
[0003] The present disclosure relates to hydroprocessing catalysts useful for the hydrodesulfurization of heavy hydrocarbon feedstocks and the hydroconversion of heavy tails fractions into distillates. The present disclosure further relates to methods of preparing the hydroprocessing catalysts. Background Art
[0004] In the processing of refined crude oil, certain fractions of heavy hydrocarbons including those having a boiling point above about 538°C (1,000°F) are subjected to catalytic hydroprocessing to remove components such as sulfur, nitrogen, metals and micro-carbon residues by desulfurization, denitrogenation, and demetallization, and to convert the heavy tail fractions into lighter distillate fractions. These processes use various types of heterogeneous hydroprocessing catalysts to promote the reaction by contacting the catalyst with the feedstock under elevated temperature and pressure conditions in the presence of hydrogen. Many conventional catalysts for providing hydroconversion and desulfurization of heavy hydrocarbon feedstocks contain a Group VIB metal component such as molybdenum and a Group VIII metal component such as cobalt or nickel supported on a refractory oxide support.
[0005] U.S. Patent No. 7,820,036 (Bhan) discloses a catalyst found to be useful for hydroprocessing heavy hydrocarbon feedstocks. The catalyst is particularly useful for hydrodesulfurization and hydroconversion of heavy hydrocarbon feedstocks and maintains stability even when used under higher process temperature conditions required for high conversion of heavier hydrocarbon fractions. The catalyst is prepared by mixing molybdenum trioxide, a nickel compound, and an inorganic oxide material and forming the mixture into calcined particles. The catalyst has up to 12 weight percent (as metal) of molybdenum and up to 4 weight percent (as metal) of nickel. An important feature of the catalyst is that its average pore size is within a specific, narrow range and the macroporosity is low. The average pore size of the catalyst disclosed herein is in the range of to The macroporosity of the catalyst is smaller than that contained in the pores with a diameter greater than There is no mention of using high molecular weight polyacrylamide in the preparation of the catalyst to prepare a catalyst with high macroporosity and enhanced catalytic properties.
[0006] U.S. Patent No. 9,114,386 (Bhan) discloses a catalyst for hydroprocessing heavy hydrocarbon feedstocks. The catalyst has a unique self-activating property such that its activity increases with use. The catalyst has relatively low concentrations of catalytic metals of molybdenum and nickel, wherein the proportion of nickel provides a low nickel to molybdenum weight ratio. The catalyst contains 1 weight percent to 10 weight percent (as metal) of molybdenum and nickel in an amount such that the nickel to molybdenum weight ratio is less than 0.4. The catalyst is characterized in that at least 1 percent and less than 10 percent of its total pore volume has pores with diameters greater than Diameter to Mesopores in the range of 1.5 to 2.5 mm / s account for at least 40% but less than 70% of the total pore volume of the catalyst. It is desirable that at least 10% of the total pore volume exists in pores with diameters in the range of 1.5 to 2.5 mm / s. to There is no mention of using high molecular weight polyacrylamide in the preparation of the catalyst to prepare a catalyst with a high macroporous pore structure, such that at least 20% of its total pore volume is in pores with a diameter greater than and have enhanced catalytic properties.
[0007] U.S. Patent No. 9,879,187 (Bhan) discloses another heavy hydrocarbon hydroprocessing catalyst having excellent catalytic performance properties. The catalyst produces a treated product having enhanced product stability, as reflected by its P value. The catalyst further has enhanced MCR removal activity and enhanced vanadium removal capacity and stability. The patent states that the unique physical characteristics of the catalyst provide its excellent catalytic properties. An important feature of the catalyst is that at least 20% of its total pore volume is contained in pores with a diameter greater than less than 70% of the total pore volume is contained in pores with a diameter of to There is no mention of using high molecular weight polyacrylamide in the preparation of the catalyst to prepare a catalyst with high macroporosity and enhanced catalytic properties. Summary of the invention
[0008] There have been efforts to develop improved catalysts for the hydroprocessing and hydroconversion of heavy hydrocarbons to produce hydroprocessed conversion products. These efforts are focused on developing improved catalysts with higher activity that provide significant conversion of the asphalt component of heavy hydrocarbon streams to lighter hydrocarbons while providing low precipitate yields.
[0009] Therefore, an ebullated bed catalyst is provided, which comprises: alumina in a range of 75 wt% to 98.5 wt% based on the weight of the ebullated bed catalyst; a molybdenum component in an amount greater than 5 wt% calculated as metal and based on the weight of the ebullated bed catalyst; and a nickel component in an amount such that the atomic ratio of nickel to molybdenum of the ebullated bed catalyst is in a range of 0.2 to 0.9. The ebullated bed catalyst has a high macroporosity pore structure such that at least 20% of the total pore volume of the ebullated bed catalyst is in pores with a diameter greater than and at least 25% of the total pore volume of the ebullated bed catalyst is in pores with a diameter greater than in the hole.
[0010] Also provided is a novel method for preparing an ebullated bed catalyst having high macroporosity and useful for converting and processing heavy hydrocarbon feeds with minimal precipitate yield. The method comprises co-grinding a molybdenum compound, catalyst fines, alumina, a high molecular weight polyacrylamide component, and water to form a co-grinded mixture capable of extrusion. The co-grinded mixture is formed into an extrudate, which is dried to provide a dried extrudate. The dried extrudate is calcined at a calcination temperature in the range of 1450°F to 1550°F to provide the ebullated bed catalyst disclosed herein. The ebullated bed catalyst has a high macroporosity pore structure such that at least 20% of the total pore volume of the ebullated bed catalyst is in pores with a diameter greater than and at least 25% of the total pore volume of the ebullated bed catalyst is in pores with a diameter greater than in the hole.
[0011] The disclosed ebullated bed hydroconversion catalyst and the catalyst prepared by the method of the present disclosure can be used in a hydroconversion process of a heavy hydrocarbon feedstock. The process includes introducing the heavy hydrocarbon feedstock into an ebullated bed reaction zone containing a bed of catalyst, wherein it is contacted with the catalyst under hydroconversion conditions. A heavy hydrocarbon conversion product is produced from the ebullated bed reaction zone. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Advantages of the present disclosure may become apparent by reading the following detailed description and by referring to the accompanying drawing, which is a simplified schematic diagram of certain aspects of an ebullated bed reactor system of the present disclosure. DETAILED DESCRIPTION
[0013] One or more specific embodiments of the present disclosure will be described below. These described embodiments are examples of currently disclosed technologies. In addition, in order to provide a concise description of these embodiments, not all features of the actual specific implementation may be described in the specification. It should be understood that in the development of any such actual specific implementation, as in any engineering or design project, many specific implementation-specific decisions will be made to achieve the specific goals of the developer, such as meeting system-related and business-related constraints, which may vary from one implementation to another. In addition, it should be understood that such development efforts may be complex and time-consuming, but are still routine tasks of design, production and manufacturing for those of ordinary skill who benefit from the present disclosure.
[0014] When introducing elements of various embodiments of the present disclosure, the articles "a," "an," and "the" are intended to indicate that there are one or more elements. The terms "comprising," "including," and "having" are intended to be inclusive, and mean that additional elements may be present in addition to the listed elements. Additionally, it should be understood that reference to "one embodiment" or "an embodiment" of the present disclosure is not intended to be interpreted as excluding the existence of additional embodiments that also incorporate the described features.
[0015] As used herein, the terms "approximately," "about," and "substantially" refer to an amount that is close to a specified amount but still performs a desired function or achieves a desired result. For example, the terms "approximately," "about," and "substantially" may refer to an amount that is less than 10% of the stated amount, less than 5% of the stated amount, less than 1% of the stated amount, less than 0.1% of the stated amount, and less than 0.01% of the stated amount.
[0016] The catalyst disclosed herein is a novel high macroporous catalyst composition useful for hydroprocessing (e.g., hydrodesulfurization, hydrodenitrogenation, and hydrodemetallization) and hydroconversion of heavy hydrocarbon feedstocks. The catalyst has particular application as an ebullated bed catalyst used in an ebullated bed process system.
[0017] The catalysts disclosed herein are capable of providing high conversion of the bitumen portion of a heavy hydrocarbon feedstock to lower boiling hydrocarbons while producing low amounts of undesirable precipitates.
[0018] The use of high molecular weight polyacrylamide in the manufacture of the catalyst and the special process steps used in the preparation of the high macroporous catalyst, such as co-grinding and controlled calcination, provide the high macroporous catalyst with a number of special properties.
[0019] While the high macroporosity and other pore structure characteristics of the catalyst are believed to contribute to the catalyst's catalytic properties in heavy feedstock processing, it is also believed that other physical properties resulting from the manner in which the high macroporosity catalyst is made also contribute to its unique properties. Thus, the disclosed method of preparing the high porosity catalyst provides a new type of high macroporosity catalyst with its enhanced properties.
[0020] The catalyst of the present disclosure includes particles. The particles can be extrudates or any other particles or shapes formed from the co-milled mixture. The particles are calcined under controlled calcination temperature conditions to provide calcined particles of a hydroprocessing catalyst having its unique pore structure.
[0021] The co-grinded mixture comprises an inorganic oxide component, a molybdenum component, a nickel component and a high molecular weight polyacrylamide. It is further desirable to include crushed catalyst fines in the mixture. These components are combined together in the specific defined concentrations and weight ratios required for the final calcined particles and the catalyst of the present disclosure.
[0022] The calcined particles further have a specifically defined pore structure as described in detail herein. The inclusion of a high molecular weight polyacrylamide in the co-milled mixture provides a final calcined particle, and thus provides an ebullated bed catalyst of the present disclosure, having an exceptionally high macroporosity pore structure and other features that contribute to enhanced catalytic properties.
[0023] The use of high molecular weight polyacrylamide is important for preparing an ebullated bed catalyst having the described high macroporous pore structure and enhanced catalytic properties. The amount of high molecular weight polyacrylamide contained in the co-grinding mixture is controlled to provide a final catalyst having the desired characteristics and properties. The amount of high molecular weight polyacrylamide contained in the co-grinding mixture should be in the range of about 0.1 wt % to about 10 wt % of the total weight of the co-grinding mixture. Preferably, the concentration of the high molecular weight polyacrylamide of the co-grinding mixture is in the range of from 0.2 wt % to 8 wt %, and more preferably the concentration is in the range of 0.4 wt % to 6 wt %.
[0024] In addition to the inorganic oxide component, the calcined particles disclosed herein also contain platinum or nickel, or both platinum and nickel. The concentration of these metals in the final catalyst composition is important for the performance of the catalyst and the use of high molecular weight polyacrylamide in the preparation of the catalyst to produce a catalyst with its unique physical properties. Therefore, the calcined particles generally contain, consist essentially of, or consist of an inorganic oxide component, a platinum component or a nickel component, or both a platinum component and a nickel component.
[0025] The molybdenum content of the calcined particles and thus the hydroprocessing catalyst, calculated as metal, should be greater than 5 weight percent (wt%) of the total weight of the calcined particles, regardless of its actual form, and less than 15 wt%. More desirably, molybdenum is present in the calcined particles in an amount ranging from 6 wt% (i.e., 9 wt%, calculated as MoO3) to 14 wt% (i.e., 21 wt%, calculated as MoO3). In a preferred embodiment, the concentration of molybdenum in the calcined particles is in the range of 7 wt% to 12 wt% (i.e., 10.5 wt% to 18 wt%, calculated as MoO3).
[0026] When present, the nickel content of the calcined particles should be in the range of 0.5% to 5% by weight calculated as metal, regardless of its actual form (i.e., 0.64% to 6.4% by weight based on nickel oxide (NiO)). Preferably, the nickel content is in the range of 0.75% to 4.5% by weight (i.e., 1% to 5.7% by weight based on nickel oxide), and more preferably 1% to 4% by weight (i.e., 1.3% to 5.1% by weight based on nickel oxide).
[0027] In embodiments of the disclosed catalyst, it may be desirable for the calcined particles to have a nickel concentration in an amount such that the weight ratio of nickel to molybdenum in the calcined particles is in the range of 0.2:1 to 0.9:1. The weight ratio is calculated and expressed on an elemental basis. However, the amount of nickel should be within the concentration range as described above, and in certain embodiments may be in the range of 0.3:1 to 0.8:1. The preferred weight ratio of nickel to molybdenum is in the range of 0.3:1 to 0.6:1.
[0028] In addition to the molybdenum, nickel and high molecular weight polyacrylamide components, the co-grinding mixture further comprises an inorganic oxide material. Any suitable porous inorganic refractory oxide that provides the desired pore structure properties for the catalyst can be used as the inorganic oxide material component of the mixture. Examples of porous inorganic refractory oxides of possible suitable types include silica, alumina and silica-alumina. Preferably alumina or silica-alumina. Most preferably alumina.
[0029] The amount of inorganic oxide material in the mixture provides an amount of inorganic oxide material in the final calcined mixture and hydroprocessing catalyst in the range of 70 weight percent to 92.5 weight percent, wherein the weight percent is based on the total weight of the calcined mixture or hydroprocessing catalyst. Preferably, the amount of inorganic oxide material in the calcined mixture is in the range of 72 weight percent to 91 weight percent, and most preferably in the range of 74 weight percent to 90 weight percent.
[0030] An important physical characteristic of the catalysts disclosed herein is that they have a relatively high macroporosity as described below. A large portion of the total pore volume of the catalyst is contained in pores having pore sizes greater than In fact, at least 18% of the total pore volume of the calcined particle or catalyst should be in pores larger than However, preferably at least 20%, and more preferably at least 22%, of the total pore volume is contained in pores with a diameter greater than in the hole.
[0031] The high porosity catalyst has a bimodal pore structure. Its pore size distribution makes it have to The first pore size peak in the pore size range and to The bimodal pore structure of the high macroporous catalyst may preferably have a second pore size peak within a pore size range of to The first pore size peak in the range of to More preferably, the first pore size peak is within the range of to The second aperture peak is in the range of to within the range.
[0032] In diameter to The percentage of the total pore volume of the catalyst contained in pores within the range of 50% to 70% of the total pore volume of the catalyst. Preferably, 45% to 65% of the total pore volume of the catalyst is contained in pores with a diameter of to More preferably, 40% to 60% of the total pore volume is contained in pores with a diameter of to in the hole within the range.
[0033] In a preferred embodiment of the catalyst, at least 18% of the total pore volume of the catalyst is contained in pores with a diameter of to Preferably, 20% to 50% of the total pore volume of the catalyst is in pores with a diameter of to More preferably, 22% to 50% of the total pore volume is contained in pores with a diameter of to in the hole within the range.
[0034] It is further desirable that the pore structure of the catalyst is such that at least 25 percent of the total pore volume is contained within macropores having diameters greater than 1,000 angstroms. It is more desirable that greater than 28 percent of the total pore volume is contained within macropores having diameters greater than 1,000 angstroms, and it is most desirable that greater than 30 percent of the total pore volume is contained within macropores having diameters greater than 1,000 angstroms.
[0035] Its diameter is larger than The percentage of the total pore volume of the catalyst comprised by the pores is greater than 30%, preferably greater than 34%, and more preferably greater than 36%.
[0036] In preparing the calcined particles of the present disclosure, the starting materials are mixed by co-grinding the components to form a co-grinded mixture. In one embodiment, the starting materials in preparing the co-grinded mixture include a molybdenum compound, a nickel compound, an inorganic oxide material, and a high molecular weight polyacrylamide.
[0037] The molybdenum compound is preferably molybdenum trioxide in the form of finely divided particles, which may be a dry powder or particles in a suspension or slurry.
[0038] The inorganic oxide material may be selected from the group consisting of alumina, silica, and alumina-silica.
[0039] The nickel component is selected from a group of suitable nickel compounds capable of being mixed with the other components of the co-milled mixture formed into particles.
[0040] The co-ground mixture is formed into particles, which are then calcined to form the calcined particles of the present disclosure. The nickel component may be nickel in the form of an oxide, such as nickel oxide, or it may be a nickel salt compound. Nickel salt compounds that may be suitably used include, for example, nickel hydroxides, chlorides, nitrates, and acetates. A preferred nickel compound for preparing the co-ground mixture is nickel nitrate.
[0041] The high molecular weight polyacrylamide used to form the co-grinding mixture is a polymer compound that can provide a catalyst of the present disclosure having high macroporosity characteristics and enhanced catalytic properties as described herein. These enhanced catalytic properties include providing significant conversion of the asphalt component of the heavy hydrocarbon feedstock and the associated low precipitate yield. The unique high macroporous pore structure of the catalyst is believed to contribute to its enhanced catalytic properties. Both the molecular weight of the polymer used to form the co-grinding mixture and its concentration in the co-grinding mixture are important for providing the final calcined particles with its high macroporosity. The critical concentration of the high molecular weight polyacrylamide required for the co-grinding mixture is as described above.
[0042] The molecular weight of the polyacrylamide used to prepare the co-grinding mixture is related to the number of repeating units in the high molecular weight polyacrylamide compound and the length of the polymer. The high molecular weight polyacrylamide should have a molecular weight in the range of 1,000,000 g / mol to 25,000,000 g / mol. The preferred molecular weight of the polyacrylamide is in the range of 1,000,000 g / mol to 20,000,000 g / mol.
[0043] It is theorized that one reason the high molecular weight polyacrylamide works is that it forms bridges between the alumina particles of the co-grinded mixture, which keeps the particles of the co-grinded mixture oriented in a spaced relationship during mixing, pelletizing or extrudate formation and calcination to produce calcined particles of the catalyst composition having the high macroporosity characteristics described herein.
[0044] Potential high molecular weight polyacrylamide compounds for preparing the composition include polymers having a molecular weight within a desired range selected from the group consisting of poly(acrylamide), poly(N-isopropylacrylamide), poly(N-octylacrylamide), poly(N-tert-butylacrylamide), poly(N-phenylacrylamide) and poly(N-sec-butylacrylamide). Among them, poly(acrylamide) is preferred.
[0045] The formation of the co-grinding mixture can be carried out by any method or means known to those skilled in the art. These include using such suitable types of solid mixers such as tumblers, fixed shells or tanks, intermittent or continuous grinder mixers and impact mixers, and using such suitable types of intermittent or continuous mixers for mixing solids and liquids or for forming extrudable pasty mixtures. Suitable types of intermittent mixers include but are not limited to can-changing mixers, fixed tank mixers, double-arm kneading mixers equipped with any suitable type of mixing blades. Suitable types of continuous mixers include single screw or twin screw extruders, tank-screw mixers and stirrers.
[0046] The mixing of the starting materials of the calcined particles can be carried out for any suitable period of time necessary to properly homogenize the co-grinded mixture. Typically, the blending time can be in the range of up to 2 hours or more than 3 hours. Typically, the blending time is in the range of 0.1 hours to 3 hours.
[0047] The term "co-grinding" as used extensively in this specification refers to mixing at least the starting materials together to form a mixture of the components of the co-grinding mixture, which is preferably a substantially uniform or homogeneous mixture of the components of such a co-grinding mixture. The scope of the term should be broad enough to include mixing the starting materials to produce a paste that exhibits properties that enable it to be extruded or formed into extrudate particles by any known extrusion method. However, the term is also intended to include mixing the starting materials to produce a mixture that is preferably substantially uniform and capable of agglomerating into formed particles. Examples of particles formed include spheroids, pills or tablets, cylinders, irregular extrudates, or only loosely bound aggregates or clusters by any method known to those skilled in the art, including but not limited to molding, tableting, pressing, granulation, extrusion, and rolling.
[0048] The majority of the molybdenum source of the calcined particles may be primarily molybdenum trioxide. In the mixing or co-grinding of the starting materials of the calcined particles, it is preferred that the molybdenum trioxide is in a finely dispersed state, either as a finely powdered solid or as finely powdered particles in a suspension or slurry. The particle size of the particulate molybdenum trioxide used to make the catalyst preferably has a maximum dimension of less than 0.5 mm (500 micrometers, μm), preferably less than 0.15 mm (150 μm) in maximum dimension, more preferably less than 0.1 mm (100 μm) in maximum dimension, and most preferably less than 0.075 mm (75 μm) in maximum dimension.
[0049] The particle size of the molybdenum trioxide used to make the calcined particles will generally have a lower size limit greater than 0.2 microns. Therefore, the particle size of the molybdenum trioxide used to form the co-grinded mixture in making the calcined particles is preferably in the range of 0.2 μm to 150 μm, more preferably in the range of 0.3 μm to 100 μm, and most preferably in the range of 0.5 μm to 75 μm. Typically, the particle size distribution of the molybdenum trioxide particles, whether in dry powder or suspension or other form, is such that at least 50 percent of the particles have a maximum dimension in the range of 2 μm to 15 μm.
[0050] Once the starting materials of the calcined particle are properly mixed and formed into shaped or formed particles, a drying step may be advantageously used to remove a certain amount of water or volatiles included in the co-milled mixture or formed particles.
[0051] Drying the formed particles may be carried out at any suitable temperature to remove excess water or volatiles, but preferably, the drying temperature will be in the range of about 75° C. to 250° C. The period of time for drying the particles is any suitable period of time necessary to provide the desired reduction in the volatile content of the particles prior to the calcining step.
[0052] The dried or undried particles are calcined in the presence of an oxygen-containing fluid such as air at a calcination temperature that provides a final calcined particle having the desired pore structure and enhanced catalytic properties described herein. The dried particles of the present disclosure are calcined at a temperature in the range of 677°C (1250°F) to 843°C (1550°C). The preferred calcination temperature is in the range of 704°C (1300°F) to 815°C (1500°F), and more preferably in the range of 746°C (1375°F) to 774°C (1425°F).
[0053] The calcined particles are particularly useful as highly active hydroprocessing catalysts for the hydroprocessing of heavy feed streams having high levels of asphalt, organometallics such as nickel and vanadium compounds, and sulfur. Prior to their use, the calcined particles may, but are not required to, be sulfided or activated by any method known to those skilled in the art. Typically, when used in the hydroprocessing of heavy hydrocarbon feedstocks, the calcined particles are contained within a reaction zone, such as a reaction zone defined by a reactor vessel, wherein the heavy hydrocarbon feedstock is contacted with the calcined particles under suitable hydroprocessing reaction conditions, and treated hydrocarbons or heavy hydrocarbon conversion products are produced therefrom.
[0054] The heavy hydrocarbon feedstock for the process disclosed herein may be derived from any high boiling point petroleum fraction, such as atmospheric tower gas oil, atmospheric tower bottoms, vacuum tower gas oil, and vacuum tower bottoms or residue.
[0055] A particularly useful aspect of the disclosed process is to provide for the hydroprocessing of heavy hydrocarbon feedstocks, which are generally defined as having a boiling temperature at their 5% distillation point, i.e., T(5), in excess of 300°C (572°F), as determined by using the test procedure described in ASTM D-1160. The present disclosure is more particularly directed to the hydroprocessing of heavy hydrocarbon feedstocks having T(5) in excess of 315°C (599°F) and even in excess of 340°C (644°F).
[0056] The heavy hydrocarbon feedstock may further include heavier hydrocarbons having boiling temperatures above 538° C. (1,000° F.) These heavier hydrocarbons are referred to herein as asphalts, and as already noted, it is recognized that one of the special features of the disclosed catalyst or process is that it is particularly effective in the hydroconversion of the asphalt content of the heavy hydrocarbon feedstock.
[0057] The heavy hydrocarbon feedstock may include as little as 10 volume percent asphalt or as much as 90 volume percent asphalt, but the amount of asphalt included in the heavy hydrocarbon feedstock is generally in the range of 20 volume percent to 80 volume percent. And, more typically, the asphalt content in the heavy hydrocarbon feedstock is in the range of 30 volume percent to 75 volume percent. The heavy hydrocarbon feedstock may further include a significantly high sulfur content.
[0058] One of the special features of the present disclosure is that it provides for desulfurization and demetallization of heavy hydrocarbon feedstocks.The sulfur content of heavy hydrocarbon feedstocks is primarily in the form of organic sulfur-containing compounds, which may include, for example, mercaptans, substituted or unsubstituted thiophenes, heterocyclic compounds or any other type of sulfur-containing compounds.
[0059] The present disclosure is characterized in that it provides for the desulfurization of heavy feedstocks having a significantly high sulfur content. Such sulfur content is typically much greater than 1 weight percent, so as to provide a treated hydrocarbon product or heavy hydrocarbon conversion product having a reduced sulfur content, such as a sulfur content of less than 1 weight percent, preferably less than 0.75 weight percent, and more preferably less than 0.5 weight percent.
[0060] When referring herein to the sulfur content of a heavy hydrocarbon feedstock or treated hydrocarbon or heavy hydrocarbon conversion product, the weight percent is determined by using test method ASTM D-4294.
[0061] The disclosed process is particularly useful for processing heavy hydrocarbon feedstocks having a sulfur content exceeding 2 weight percent, and with such heavy hydrocarbon feedstocks, the sulfur content may be in the range of 2 weight percent to 8 weight percent. The catalysts and processes disclosed herein are particularly useful for processing heavy hydrocarbon feedstocks having a particularly high sulfur content exceeding 3 weight percent or even 4 weight percent and in the range of 3 weight percent to 7 weight percent or even 4 weight percent to 6.5 weight percent.
[0062] The process utilizes the high macroporous catalyst disclosed herein in the hydroprocessing of heavy hydrocarbon feedstocks to provide desulfurization, denitrification and asphalt conversion simultaneously with reduced or low precipitate yield. In the process, the heavy hydrocarbon feedstock is contacted with the catalyst under suitable hydrodesulfurization and hydroconversion process conditions to produce heavy hydrocarbon conversion products.
[0063] The nickel content of the heavy hydrocarbon feedstock is typically in the form of an organonickel compound. The nickel concentration of the heavy hydrocarbon feedstock may be in the range of 2 ppmw to 250 ppmw. More typically, the heavy hydrocarbon feedstock of the disclosed process has a nickel concentration in the range of 5 ppmw to 225 ppmw, and most typically, the nickel concentration is in the range of 7 ppmw to 200 ppmw.
[0064] The heavy hydrocarbon feedstock may also have a vanadium concentration generally in the range of 5 ppmw to 250 ppmw. It is desirable that the heavy hydrocarbon feedstock contain as little vanadium as possible, but the composition provides demetallization and thus removal of vanadium from the heavy hydrocarbon feedstock. More typically, the vanadium concentration of the heavy hydrocarbon feedstock is in the range of 10 ppmw to 225 ppmw.
[0065] The heavy hydrocarbon conversion product should have a sulfur content lower than the reduction of the heavy hydrocarbon feedstock. The reduced sulfur content is preferably less than 1 weight percent sulfur concentration. However, it should be recognized that the disclosed process can have the ability to effectively desulfurize the heavy hydrocarbon feedstock to provide a treated hydrocarbon or heavy hydrocarbon conversion product with a reduced sulfur content of less than 0.5 weight percent and even less than 0.4 weight percent of the heavy hydrocarbon conversion product. The precipitate usually produced with the heavy hydrocarbon conversion product is less than 0.5 weight %, and preferably less than 0.4 weight %, as measured by test method ASTM-4870. The process disclosed herein using a high macroporous hydroprocessing catalyst provides a heavy hydrocarbon conversion product with a significantly lower precipitate content than the comparative catalyst. The precipitate content of the heavy hydrocarbon conversion product may even be less than 0.35 weight % or less than 0.3 weight % of the heavy hydrocarbon conversion product.
[0066] The calcined particles (high macroporosity catalysts) of the present disclosure can be used as part of any suitable reactor system that provides contact of the catalyst with a heavy hydrocarbon feedstock under suitable hydroprocessing conditions, which can include the presence of hydrogen and elevated total pressure and temperature. Such suitable reaction systems can include fixed catalyst bed systems, ebullating catalyst bed systems, slurry catalyst systems, and fluidized catalyst bed systems.
[0067] The catalysts disclosed herein are particularly useful as ebullated bed catalysts for use in an ebullated bed reactor system.An ebullated bed reactor system is described in more detail with reference to the accompanying drawings.
[0068] Another suitable reactor system comprises a fixed bed of the disclosed catalyst contained within a reactor vessel. The reactor vessel is equipped with a reactor feed inlet means, such as a feed nozzle, for introducing a heavy hydrocarbon feedstock into the reactor vessel, and a reactor effluent outlet means, such as an effluent outlet nozzle, for withdrawing a reactor effluent or a heavy hydrocarbon conversion product from the reactor vessel.
[0069] The process is typically operated at a hydroprocessing (hydroconversion and hydrodesulfurization) reaction pressure in the range of 2298 kPa (300 psig) to 20,684 kPa (3000 psig), preferably in the range of 10,342 kPa (1500 psig) to 17,237 kPa (2500 psig), and more preferably in the range of 12,411 kPa (1800 psig) to 15,513 kPa (2250 psig). The hydroprocessing reaction temperature is typically in the range of 340°C (644°F) to 480°C (896°F), preferably in the range of 360°C (680°F) to 455°C (851°F), and most preferably in the range of 380°C (716°F) to 425°C (797°F).
[0070] The heavy hydrocarbon feedstock is fed to the reaction zone of the process at a flow rate that is typically such as to provide 0.01 hour -1 Up to 3 hours -1 As used herein, the term "liquid hourly space velocity" means the rate at which the heavy hydrocarbon feedstock is charged to the process reaction zone (in volume per hour) divided by the volume of catalyst contained in the reaction zone charged with the heavy hydrocarbon feedstock. The preferred LHSV is between 0.05 hours and 1 hour. -1 Up to 2 hours -1 In the range of 0.1 hours - 1 to 1.5 hours -1 and most preferably within 0.2 hours -1 Up to 0.7 hours -1 within the range.
[0071] It is preferred to charge hydrogen with the heavy hydrocarbon feedstock into the reaction zone of the process disclosed herein. In this case, the hydrogen is sometimes referred to as the hydrogen treat gas. The hydrogen treat gas rate is the amount of hydrogen relative to the amount of heavy hydrocarbon feedstock charged to the reaction zone and is generally in the range of up to 1781 m 3 / m 3 The process gas velocity is preferably within the range of 89 m / s. 3 / m 3 (500SCF / bbl) to 1781m 3 / m 3 (10,000 SCF / bbl), more preferably 178m 3 / m 3 (1,000SCF / bbl) to 1602m 3 / m 3 (9,000 SCF / bbl), and most preferably 356m 3 / m 3 (2,000SCF / bbl) to 1425m 3 / m 3 (8,000SCF / bbl).
[0072] The drawing presents a simplified schematic diagram of an ebullated bed reactor system 10 in which the high porosity catalyst of the present disclosure is used. The ebullated bed reactor system includes an elongated vessel 12 defining several zones, such as a contact zone for contacting a heavy hydrocarbon feedstock with the high porosity catalyst under suitable hydroconversion reaction conditions, and a separation zone for separating a hydrotreated heavy hydrocarbon product from the high porosity catalyst.
[0073] Within elongated vessel 12 is a settled high macroporosity catalyst bed 14 having a settled high macroporosity catalyst bed level 16. A reactor feed comprising a heavy hydrocarbon feedstock and hydrogen is introduced through conduit 18 into a lower zone 17 located within elongated vessel 12 below the ebullient catalyst bed.
[0074] The reactor feed passes through a horizontal distributor plate 20 which provides a means for directing the reactor feed upward and through the settled high porosity catalyst bed 14. The reactor feed passes through the settled high porosity catalyst bed 14 which acts to lift and expand the high porosity catalyst bed, thereby providing an expanded high porosity catalyst bed 22 (boiling catalyst bed) having an expanded high porosity catalyst bed level 24.
[0075] In the separation zone 26 of the elongated vessel 12 , the high macroporosity catalyst is separated from the liquid hydrocarbons 28 having a liquid level 30 and the heavy hydrocarbon conversion products which flow out of the elongated vessel 12 through a conduit 32 .
[0076] Downcomer 34 within elongated vessel 12 provides conduit means for recycling liquid hydrocarbons 28 to the bottom of expanded high porosity catalyst bed 22. Conduit 36 is operably connected in fluid flow communication between downcomer 34 and ebullient pump 38. Ebullient pump 38 provides means for recycling and circulating liquid hydrocarbons 28 through expanded hydroconversion catalyst bed 22.
[0077] The upper end of the elongated vessel 12 includes a catalyst inlet conduit means 40 for introducing fresh high porosity catalyst while the ebullated bed reactor system 10 is in operation. Fresh high porosity catalyst may be introduced into the elongated vessel 12 through the conduit means 40 via a conduit 42. The lower end of the elongated vessel 12 includes a catalyst outlet conduit means 44 for removing used high porosity catalyst while the ebullated bed reactor system 10 is in operation. Used high porosity catalyst flows out of the elongated vessel 12 via a conduit 46.
[0078] The following examples further illustrate the present disclosure, but they should not be construed as limiting the scope of the embodiments disclosed herein.
[0079] Example
[0080] Embodiment 1
[0081] This Example I illustrates the preparation methods and catalyst compositions of the disclosed catalysts and comparative catalysts.
[0082] Catalyst composition of the present invention
[0083] The disclosed catalyst composition embodiment is prepared by mixing 932.2 grams of alumina powder having a LOI of 23.9% with 20 grams of a high molecular weight polyacrylamide component ( 133M nonionic flocculant), 210.7 grams of catalyst fines (finely ground aluminum oxide, molybdenum oxide and nickel oxide powders), 75.2 grams of molybdenum trioxide and 78.8 grams of nickel nitrate are mixed in a grinder. The grinder is run for about one minute before adding a mixture of 1354.5 grams of water and 29.4 grams of 68% nitric acid. The mixture is ground for 10 minutes, then 20 grams of a lower molecular weight cationic dispersant is added and the mixture is ground for another 15 minutes. The mixed material is extruded using a screw extruder to prepare cylindrical spheres. The extruded material is dried in an oven at 250°F for 1 hour. The material is calcined in a muffle furnace at a temperature of 1390°F to 1415°F for one hour. The metal loading of the final catalyst includes 2.9 weight % nickel and 12.1 weight % molybdenum, both values based on oxides.
[0084] Comparative Catalyst Compositions
[0085] A comparative catalyst composition was prepared by mixing 2721.6 parts (2049.4 parts on a dry basis) of alumina powder and 594.3 parts (563.5 parts on a dry basis) of finely ground alumina, molybdenum oxide and nickel oxide powders with a molybdenum component mixture of 539.1 parts of ammonium heptamolybdate (27% MoO3) and 1406.2 parts of water and a nickel component mixture of 333.3 parts of nickel nitrate solution, 81.1 parts of 70% nitric acid and 1406.2 parts of water in a grinder. These components were ground for 30 minutes, followed by the addition of 14.1 parts of a flocculant (Superfloc LMW 300), followed by mixing for 5 minutes. The co-ground mixture was then extruded into extrudates, which were dried in air at a temperature of approximately 250°F for about 1 hour. The dried extrudates were then calcined in air at a temperature of 1370°F for 1 hour. The metal loading of the final catalyst included 3.0 wt% nickel and 9.0 wt% molybdenum, both values based on the oxides.
[0086] Table 1 below presents the pore structure properties of the catalysts of the invention and comparative catalysts.
[0087] Table 1 - Pore structure properties of the inventive and comparative catalysts
[0088]
[0089] *Total pore volume (TPV)
[0090] Example II
[0091] This Example II describes the conditions for performance testing of a comparative catalyst and a catalyst of the present invention and the results of the performance testing.
[0092] The catalyst was tested in a 2-stage CSTR pilot plant. The properties of the feed are summarized in Table 2 and the process conditions are presented in Table 3.
[0093] Table 2 - Properties of feeds used to evaluate catalysts
[0094] nature value 1000 F.+, weight% 87.7 Sulfur, weight % 5.255 MCR, weight % 20.8 Nickel, wppm 43 Vanadium, wppm 130 Feed density, g / ml 1.0347 n-C7 insoluble matter, wt% 12.7 n-CS insoluble matter, weight % 20.9
[0095] Table 3 - Process conditions used to evaluate catalysts
[0096] <![CDATA[Catalyst LHSV, hr- 1 > 0.55 Total pressure, psia 2250 H2 / oil ratio, scft / bbl 4090 Temperature, °F 795
[0097] The performance of the catalysts of the invention is summarized in Table 4 relative to the performance of the comparative catalyst (base).
[0098] Table 4 - Relative performance of catalysts
[0099] Comparison of catalysts Catalyst of the present invention Sulfur conversion, weight % 100 103 968 F+ conversion 100 112 698 F+ fraction sediment (ASTM D 4870) 100 65
[0100] The review of the performance results presented in Table 4 shows that the conversion and desulfurization catalytic performance of the catalyst of the present invention is superior to that of the comparative catalyst. Compared with the comparative catalyst, the catalyst of the present invention further provides a huge improvement in the precipitate yield (i.e., a reduction in the precipitate yield). The catalyst of the present invention unexpectedly provides 65% of the precipitate yield provided by the comparative catalyst. Therefore, the precipitate yield is reduced by 35% compared to that provided by the comparative catalyst. These results show that the catalyst of the present disclosure prepared using high molecular weight polyacrylamide with its unique pore structure and high macroporosity unexpectedly provides a low precipitate yield while providing material improvements in conversion and desulfurization.
Claims
1. A method for preparing an ebullated bed catalyst having high macroporosity and useful for converting and processing heavy hydrocarbon feeds with reduced precipitate yield, wherein the method comprises: co-milling a molybdenum compound, a hydroprocessing catalyst fine powder, alumina, a high molecular weight polyacrylamide component having a molecular weight range of 1,000,000 g / mol to 25,000,000 g / mol, and water to form a co-milled mixture; extruding the co-milled mixture to form an extrudate; drying the extrudate to provide a dried extrudate; The dried extrudate is calcined at a calcination temperature in the range of 1450°F to 1550°F to provide the ebullated bed catalyst, wherein the ebullated bed catalyst has a high macroporosity pore structure such that at least 18% of the total pore volume of the ebullated bed catalyst is in pores having a diameter greater than 5,000 Å and at least 25% of the total pore volume of the ebullated bed catalyst is in pores having a diameter greater than 1,000 Å.
2. The method of claim 1, wherein the high macroporosity pore structure has a bimodal pore size distribution defined as having a first pore size peak in the range of 40 Å to 250 Å and a second pore size peak in the range of 5,000 Å to 11,000 Å.
3. The method of claim 1, wherein at least 30% of the total pore volume of the ebullated bed catalyst is in pores having a diameter greater than 250 Å.
4. The method of claim 3, wherein 50% to 70% of the total pore volume of the ebullated bed catalyst is within the pore diameter range of 40Å to 250Å, and 18% to 60% of the total pore volume of the ebullated bed catalyst is within the pore diameter range of 5,000Å to 11,000Å.
5. The method of claim 1, comprising controlling the pH of the co-milled mixture, wherein the pH is controlled within the range of 4.5 to 12.
6. The process of claim 1 wherein the hydroprocessing catalyst fines comprise a pulverized finished hydroprocessing catalyst comprising molybdenum, nickel, phosphorus and alumina in powder form, the molybdenum compound being molybdenum trioxide powder in a finely dispersed state of particulate molybdenum trioxide, a finely dispersed powdered solid or a suspension, and wherein the particle size of the particulate molybdenum trioxide has a maximum dimension of less than 500 μm.
7. The process of claim 6, wherein the ebullated bed catalyst comprises molybdenum in an amount greater than 5 wt% and less than 15 wt% calculated as metal and based on the weight of the ebullated bed catalyst.
8. The method of claim 6, wherein the ebullated bed catalyst comprises nickel such that the atomic weight ratio of nickel to molybdenum is in the range of 0.2 to 0.
9.
9. The method of claim 1, wherein the concentration of the high molecular weight polyacrylamide in the co-milled mixture is in the range of 0.1 wt% to 10 wt% based on the dry weight of the co-milled mixture.
10. An ebullated bed catalyst, prepared by the method according to any one of claims 1 to 9, the ebullated bed catalyst comprising: alumina, the alumina ranging from 75 wt % to 98.5 wt % based on the weight of the ebullating bed catalyst; a molybdenum component in an amount greater than 5% by weight, calculated as the metal and based on the weight of the ebullating bed catalyst; and a nickel component in an amount such that the ebullated bed catalyst has an atomic ratio of nickel to molybdenum in the range of 0.2 to 0.9, wherein the ebullated bed catalyst has a high macroporosity pore structure such that at least 18% of the total pore volume of the ebullated bed catalyst is in pores having a diameter greater than 5,000 Å and at least 25% of the total pore volume of the ebullated bed catalyst is in pores having a diameter greater than 1,000 Å; as well as A bimodal pore size distribution is defined as having a first pore size peak in the range of 40 Å to 100 Å and a second pore size peak in the range of 5,000 Å to 11,000 Å.
11. The ebullated bed catalyst of claim 10, wherein at least 30% of the total pore volume of the ebullated bed catalyst is in pores having a diameter greater than 250 Å.
12. The ebullated bed catalyst of claim 10, wherein 50% to 70% of the total pore volume of the ebullated bed catalyst is in pores having pore diameters ranging from 50Å to 200Å, and 18% to 60% of the total pore volume of the ebullated bed catalyst is in pores having pore diameters ranging from 5,000Å to 11,000Å.
13. The ebullated bed catalyst according to any one of claims 10 to 12, comprising: molybdenum in an amount greater than 5 wt% and less than 15 wt% calculated as metal and based on the weight of the ebullated bed catalyst; and nickel such that the atomic weight ratio of nickel to molybdenum is in the range of 0.2 to 0.9.
Citation Information
Patent Citations
Highly stable heavy hydrocarbon hydrodesulfurization catalyst and methods of making and use thereof
US7820036B2
Self-activating hydroprocessing catalyst and process for treating heavy hydrocarbon feedstocks
US9114386B2
Hydroprocessing catalyst, method of making, and process for treating heavy hydrocarbon feedstocks
US9879187B2
Hydroprocessing catalyst and process for treating heavy hydrocarbon feedstocks
US20130284640A1